The Effect of Health Education on Low Fat Diets through Video Media on Knowledge Level in Cholesterol Sufferers - Retnosari, Merlina; Yuniartika, Wachidah (Jurnal Kesehatan, 2024)
Hypercholesterolemia is still a health problem that can lead to complications such as hypertension, coronary heart disease, and stroke, but it can be controlled by modifying lifestyle. Health education in the form of video media counseling can be done to increase knowledge and awareness to change one's behavior. This study aimed to determine the effect of health education on a low-fat diet through video media on the level of knowledge. This study used a quasi-experiment with a one-group pre and post-test design. The sample used was 33 respondents using the purposive sampling technique. The research was conducted from June to July 2024. Using the Dyslipidemia Dietary Knowledge Questionnaire (DDKQ), which was developed, the results of corrected item-total correction >0.632 with Cronbach's alpha >0.60, namely 0.941. Inclusion criteria are the results of checking cholesterol levels before giving intervention (200mg/dl), willingness to be a respondent, the category of knowledge is less and enough, can do activities independently, and has a cellphone. Exclusion criteria have comorbidities and do not follow the flow of research until the end. Data analysis using univariate analysis and the Wilcoxon signed rank test. Based on the Wilcoxon Signed Ranks test results, the p-value is 0.001, which is <0.05. There is an effect of health education on a low-fat diet through videos on the level of knowledge in cholesterol sufferers.